Effect of leisure-time physical activity on depression and depressive symptoms in menopausal women: a systematic review and meta-analysis of randomized controlled trials - Rong Liu; Xun Tang (Frontiers in Psychiatry)
AimsMenopausal women often suffer from depression, which impairs their quality of life. Physical activity has been reported to exert beneficial effects on preventing and treating depression. This meta-analysis aims to explore the effect of leisure-time physical activity on determined depression or depressive symptoms in menopausal women.MethodsRelevant studies were searched from PubMed, Embase, Cochrane Library, Web of Science, PsycINFO, CINAHL Plus, China National Knowledge Infrastructure (CNKI), VIP, and WanFang databases. Outcomes were depression or depressive symptoms. Weighted mean difference (WMD) or standard mean difference (SMD) with 95% confidence interval (CI) was used as the statistical measure. Heterogeneity tests were performed for each outcome, and all outcomes were subjected to sensitivity analysis. Subgroup analysis was performed based on depression degree, exercise intensity, exercise form, intervention duration, supervision, sample size, and geographical region.ResultsA total of 17 studies were included in this meta-analysis. The results showed that exercise alleviated the depressive symptoms of menopausal women (SMD = −1.23; 95% CI, −2.21 to −0.24). In addition, exercise was found to reduce the depression (SMD = 11.45; 95% CI, −1.75 to −1.15), and depression assessed by the Center for Epidemiologic Studies Depression Scale (CES-D) (WMD = −5.76; 95% CI, −6.63 to −4.89) or Self-Rating Depression Scale (SDS) (WMD = −6.86; 95% CI, −9.24 to −4.49). The results were similar regardless of depression degrees, exercise intensity, intervention duration, exercise form, supervision or not, sample size, and geographical region.ConclusionsLeisure-time physical activity may help alleviate depressive symptoms or depression in menopausal women. However, further high-quality studies are needed to confirm these findings and better understand the specific effects of physical activity on depression in this population.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024581087.